A Study of Finite Element Analysis For The Thermal Distribution of Friction Stir Welding - King, Eric; Ahmad, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The Friction Stir Welding (FSW) is a thermal-mechanical, solid state joining technique, which developed into viable technology for the development of sheet and sheet material, including plate materials, for applications in various industries, including plating or plate materials, for use in different industries. This study focused on thermal distribution modeling to better understand thermal distribution during friction stir welding in relation to welding parameters. The key parameters that are taken into account are the rotational speed of the tool and the travel speed. The temperature distribution in the friction stir welding process was simulated using the Finite Element Method (FEM) software, Abaqus Unified FEA. The results show that the higher the tool’s rotation speed, the more heat is distributed around the surface of the welding plate. The outcome of this research provide a knowledge of the thermal distribution along the surface of the welding plate using finite element analysis.